A novel Tembusu virus isolated from goslings in China form a new subgenotype 2.1.1. Issue 4 (29th May 2021) - Zhu, Yingqi; Hu, Zengjin; Lv, Xuan; Huang, Rong; Gu, Xiangxue; Zhang, Chong; Zhang, Miao; Wei, Juanwen; Wu, Qiong; Li, Jiaming; Zhang, Ruichen; Cao, Shoulin; et al.
Abstract: Since 2010, several duck Tembusu viruses (DTMUVs) have been isolated from infected ducks in China, and these virus strains have undergone extensive variation over the years. Although the infection rate is high, the mortality rate is usually relatively low—~5%–30%; however, since fall 2019, an infectious disease similar to DTMUV infection but with a high mortality rate of ~50% in goslings has been prevalent in Anhui Province, China. The present study identified a new Tembusu virus, designated DTMUV/Goose/China/2019/AQ‐19 (AQ‐19), that is believed to be responsible for the noticeably high mortality in goslings. To investigate the genetic variation of this strain, its entire genome was sequenced and analysed for specific variations, and goslings and mice were challenged with the isolated virus to investigate its pathogenicity. The AQ‐19 genome shared only 94.3%–96.9% and 90.9% nucleotide identity with other Chinese and Malaysian DTMUVs, respectively; however, AQ‐19 has high homology with Thailand DTMUVs (97.2%–98.1% nucleotide identity). Phylogenetic analysis of the E gene revealed that AQ‐19 and most of Thailand DTMUVs form a branch separate from any of the previously reported DTMUV strains in China. After the challenge, some goslings and mice showed typical clinical signs of DTMUV, particularly severe neurological dysfunction. AQ‐19 has high virulence in goslings and mice, resulting in 60% and 70% mortality through intramuscular and intracerebral routes, respectively. Pathological examination revealed severe histological lesions in the brain and liver of the infected goslings and mice. Taken together, these results demonstrated the emergence of a novel Tembusu virus with high virulence circulating in goslings in China for the first time, and our findings highlight the high genetic diversity of DTMUVs in China. Further study of the pathogenicity and host range of this novel Tembusu virus is particularly important.